The Relationship between Corporate Sustainability and Corporate Financial Performance: A conceptual review - Shamil, M.; Shaikh, Junaid; Ho, Poh-Ling; Krishnan, Anbalagan (School of Social Sciences, Universiti Sains Malaysia, 2012)
Corporate sustainability is emerging as a separate body of knowledge influenced by wider application in firms and industries, supported by global initiatives. So far studies have focused on the linear relationship between sustainability performance and corporate financial performance. However the results of such studies are mixed and only few studies examined the non-linear relationship between sustainability performance and corporate financial performance. Further most studies adopted sustainability performance either as a predictor variable or as an outcome variable. Understanding the direct relationship between corporate sustainability and corporate financial performance is becoming important as firms are identifying corporate sustainability as a strategic goal and is increasingly being embedded into firm operations. Further it’s of importance to understand whether the relationship between corporate sustainability and corporate financial performance is influenced by other factors and whether the relationship can be explained better through such interacting factors.Hence this paper focuses on whether a firms integration capability, drawn from dynamic capability theory can explain whether firms with higher level of integration capability can demonstrate a direct relationship between corporate sustainability and corporate financial performance. Thus a conceptual framework incorporating corporate sustainability adoption as a predictor variable, corporate financial performance as a criterion variable, sustainability performance as a mediator between corporate sustainability adoption and corporate financial performance and integration capability as a moderator between corporate sustainability adoption and corporate financial performance is proposed. The conceptual framework proposed in this study provides the opportunity to test the model indifferent contexts using primary data and should promote further discussion on investigating the non-linear relationship between corporate sustainability adoption and corporate financial performance and to propose theoretical frameworks incorporating constructs from other organizational theories.